PENGARUH PENCUCIAN TERHADAP TRANSESTERIFIKASI MINYAK JELANTAH MENGGUNAKAN KATALIS KALIUM HIDROKSIDA - , RIZKI PRATAMA PUTRA; , drh. Aris Purwantoro, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The fuel demand increases over time, while the deposit of fossil fuel is limited. The solution is seeking renewable energy, for instance processed used cooking oil into biodiesel. The aim of this research is to study the effects of washing towards transesterification of used cooking oil using potassium hydroxide catalyst and test the biodiesel quality based on ASTM and SNI standards. Four samples of used cooking oil were collected from various sources in Yogyakarta. The samples were titrated to count KOH amount to be added in titration step (z gram KOH). The mixture of isopropanol and phenolphtalein was used as indicator. Transesterification was done by mixing 1 litre used cooking oil, 200 ml methanol, and 7+z gram KOH. The mixture was transferred into waterbath and shaked it 500 rpm for 60 minutes at 55oC, then separated the fatty acid methyl esther and gliserol using funnel for 24 hours. The washing step was done by mixing 500 ml FAME and 250 ml warm aquadest 45oC, then separated the FAME and aquadest using funnel for 24 hours. The next step is warmed the FAME using waterbath at 55oC for 5 hours. Finally, the samples were sent to the Laboratory of Oil, Gas, and Coal, Department of Chemical Engineering, Faculty of Engineering, Universitas Gadjah Mada to test the FAME quality. The results show that the samples are in accordance the standards of specific gravity, flash point, and copper strip corrosion parameters, but it could not meet cloud point, carbon residue, ash residue, and water content parameters. Thus, it concluded that the washing has effect on transesterification of used cooking oil using potassium hydroxide catalyst.